Impatience and Savoring vs. Dread: Asymmetries in Anticipation Explain Consumer Time Preferences for Positive vs. Negative Events - Hardisty, David J.; Weber, Elke U. (Journal of Consumer Psychology, 2020)
For positive experiences (e.g., when to eat a snack), consumers generally prefer to have them immediately, and for negative experiences (e.g., when to pay a bill), consumers often prefer to delay. Yet, across three studies (plus twelve supplemental studies) we find that anticipatory feelings push in the opposite direction, and do so differently for positive vs. negative events, leading to different time preferences: The desire for immediate positives is stronger than the desire to delay negatives. For negative events, anticipatory utility is strongly negative, reducing the desire to delay bad things (i.e., consumers want to “get it over with” to minimize the psychological discomfort), but for positive events, overall anticipatory utility is weakly positive, and therefore does little to reduce consumers’ desire to expedite good things. This anticipatory asymmetry happens because when consumers think about a future positive event, they both enjoy imagining it (savoring) while simultaneously disliking the feeling of waiting for it (impatience), but when consumers think about a negative event, they both dislike imagining it (dread) and dislike the feeling of waiting for it. We demonstrate the managerial implications of these findings in a pair of field studies using online advertisements for retirement planning.